UTILIZATION OF VEGETABLE HYDROCOLLOID COMPOUNDS AS EDIBLE COATING MATERIAL TO EXTEND THE SHELF LIFE OF BANANAS MULI (Musa acuminata Linn.) - Desi Nurjannah; Muh. Akhsan Akib; Nur Ilmi (Agrotech Journal, 2018)
The preserve quality, freshness and extending shelf life of fruit could be done by storing the fruits in the refrigerated room, pressurized room or by modifying the atmosphere of the room. However, this type of storage cost is quite expensive, therefore needed another solution that is fruit coating using edible coating solution made from vegetable hydrocolloids. The aims of this study were to determine the best materials type among the three types of vegetable hydrocoloid materials, namely extract Aloe vera leaves, extract Ceiba pentandra leaves and extract  Abelmoschus manihot leaves that are able to preserve the shelf life of M.acuminata fruit. This research use was a complete randomized design with four treatments, namely;  without edible coating, edible coating of extract Aloe vera leaves, edible coating of extract Ceiba pentandra leaves, and edible coating of extract  Abelmoschus manihot leaves, with three replications. The result showed that the lowest shrinkage percentage was found in edible coating of extract Aloe vera leaves with an average value of 3.43% and the highest was found in treatment without edible coating of 4.37%. At the end of observation the highest sugar content was obtained in edible coating of extract Aloe vera leaves of 20 oBrix while the lowest was in treatment without edible coating that was 16oBrix. In organoleptic test, panelists prefered edible coating of extract Aloe vera leaves with an value range of 4 or 5 equivalented with neutral or likes, and did not like of edible coating of wxtract Abelmoschus manihot leaves  with an value range of 3 or 4 equivalented with slightly dislike  or neutral. Based on the conducted observational, the edible coating of extract Aloe vera leaves was able to preserve the shelf life of M.acuminata fruit up to five days after harvesting